USE OF LOGISTIC REGRESSION IN IDENTIFYING PRIORITIES FOR REGIONAL INVESTMENT POLICY IN RESPECT OF FOREIGN INVESTORS IN THE REGIONS OF THE RUSSIAN FEDERATION - Lilia V. Matraeva (Статистика и экономика, 2016)
This paper focuses on the problems of the study of the investment climate in the country and the regions. Since the possibility of statistical assessment of the investment climate is itself under discussion due to the subjectivity of instruments used to measure it, the article attempts to develop a model that reflects the impact of the investment instruments of regional policy on flows of foreign direct investments, i.e. not to solve the general problem of measurement of the investment climate in the region, but to solve the particular one - what incentive tools are the most in demand by foreign investors in the particular area or region.